Turkish foreign policy and its regional implications - Altunışık, Meliha Benli (Emirates lecture, 2011)
This paper examines the elements of a new Turkish foreigpolicy in the Middle East and focuses on the reasons for its evolution as well as its structural conditions and political leadership. In discussing these factors this paper aims to identify the circumstances that have created an opening for change. It is argued that those structural conditions which emerged at the beginning of the new millennium coincided with a strategic political leadership that led to this transformation